2003
DOI: 10.1007/s00586-003-0538-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of venous thromboembolism in spinal surgery

Abstract: Deep vein thrombosis (DVT), and its most feared complication, pulmonary embolism (PE), still have a high incidence with high risk for patients' health. Proven prophylactic measures are available but are generally underused, and DVT is still considered the most common cause of preventable death among hospitalized patients. The rationale for prophylaxis of venous thromboembolism is based on the clinically silent nature of the disease, the relatively high prevalence among hospitalized patients and the potentially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
1
13

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(73 citation statements)
references
References 76 publications
3
56
1
13
Order By: Relevance
“…Previous studies have reported incidence rates of between 0.5% and 2.5%, but these have been restricted to small patient series (Lea et al 1978, Rokito et al 1996, Dearborn et al 1999, Oda et al 2000. We found a rate of 2.2% (n 22) over the 25-year period, which is similar to results reported in the literature (Lea et al 1978, Dearborn et al 1999, Brambilla et al 2004). When we planned this retrospective study, we assumed that there would be a significantly higher rate of clinically evident thromboembolic complications, as we had had 2 cases of fatal pulmonary embolism in a time period of 4 months.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Previous studies have reported incidence rates of between 0.5% and 2.5%, but these have been restricted to small patient series (Lea et al 1978, Rokito et al 1996, Dearborn et al 1999, Oda et al 2000. We found a rate of 2.2% (n 22) over the 25-year period, which is similar to results reported in the literature (Lea et al 1978, Dearborn et al 1999, Brambilla et al 2004). When we planned this retrospective study, we assumed that there would be a significantly higher rate of clinically evident thromboembolic complications, as we had had 2 cases of fatal pulmonary embolism in a time period of 4 months.…”
Section: Discussionsupporting
confidence: 81%
“…It is widely accepted that general risk factors such as age, sex, obesity and tobacco consumption increase the risk of developing thromboembolic complications (Ferree and Wright 1993, Smith et al 1994, Rokito et al 1996, Lee et al 2000, Oda et al 2000, Andersson and Spencer 2003, Brambilla et al 2004). We found that deep venous thrombosis and pulmonary embolism were more common in older patients, and in males, and also in patients with obesity and regular smoking.…”
Section: Discussionmentioning
confidence: 99%
“…The neurosurgery community has not developed a unified approach for the prevention of VTE thrombo-prophylaxis in this population [10]. While there is no doubt that stockings and…”
Section: Introductionmentioning
confidence: 99%
“…the lack of precise literature. [37][38][39] Our research uncovered only one study with level 1 evidence, in which Wood et al 28 compared the use of pneumatic compression stockings with the use pneumatic thigh compression bandages. Although a control group was not used, the authors found lower rates of incidence of DVT and PTE than those found in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…Other factors described in the literature, and that lead to an increased risk of DVT, include surgical time, longer periods of postoperative immobility, and ventral decubitus. 24,37,40 Patient demographics are also an important factor contributing to the risk of DVT. Advanced age, male sex, presence of other comorbidities, such as congestive heart failure (CHF), and recent weight loss are independently associated with an increase in the rate of DVT complications.…”
Section: Resultsmentioning
confidence: 99%